2018
DOI: 10.1021/acs.analchem.8b02904
|View full text |Cite
|
Sign up to set email alerts
|

Alternating-Current-Driven Microplasma for Multielement Excitation and Determination by Optical-Emission Spectrometry

Abstract: Microplasma optical-emission spectrometry (OES) is a promising technique for developing portable analytical instrumentations for real-time and on-site measurement of trace elemental species. However, its analytical performance is far from satisfactory for multielement analysis. Herein, a miniature OES system is developed for simultaneous multielement analysis with alternating-current-driven microplasma generated on the nozzle of a pneumatic micronebulizer as the excitation source. Because of the strong excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Generation of Volatile Species of Se, Ag, Sb, Pb, and Bi by Using LSDBD−CVG. The research work of our group 28,29 and Yu et al 30,31 demonstrated that improving the interaction between the solution and plasma would greatly enhance the plasma-induced vapor generation efficiency and plasma excitation capability. Therefore, a micronebulizer was used in the present study to further improve the nebulization efficiency and, more importantly, to reduce the sample consumption.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Generation of Volatile Species of Se, Ag, Sb, Pb, and Bi by Using LSDBD−CVG. The research work of our group 28,29 and Yu et al 30,31 demonstrated that improving the interaction between the solution and plasma would greatly enhance the plasma-induced vapor generation efficiency and plasma excitation capability. Therefore, a micronebulizer was used in the present study to further improve the nebulization efficiency and, more importantly, to reduce the sample consumption.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…For Sb measurement with microplasma-OES, HG is typically employed to form "pure" and "dry" Sb hydride to achieve s u ffi c i e n t s e n s i t i v i t y f o r e n v i r o n m e n t a l s a mples. 10,14,18,[30][31][32]42,43 In our proposed hydrogen-doped SAGD-OES method, direct sensitive determination of Sb in water samples is feasible as the vapor generation and excitation of Sb occur simultaneously in SAGD, which eliminates the use of HG and thus greatly benefits the portability of the whole system. As shown in Table 1, the LOD of hydrogen-doped SAGD-OES is comparable to that of other reported micro-plasma sources coupled with HG, including SCGD, PD, APGD, and SAGD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Table 1, the LOD of hydrogen-doped SAGD-OES is comparable to that of other reported micro-plasma sources coupled with HG, including SCGD, PD, APGD, and SAGD. 10,14,18,[30][31][32]42,43 Although the LOD was about 1 order of magnitude higher than that of HG-ICP-OES, the proposed method is simple, green, low-cost, and with satisfactory sensitivity to be further developed into a portable form for on-site trace Sb analysis. 44 Compared with SCGD with direct solution introduction, the LOD is improved more than 3 orders of magnitude (2100 to 0.85 μg L −1 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Over the past few decades, significant efforts have been devoted to developing efficient sampling techniques for improving the sensitivity and anti-interference capability of atomic spectrometry. Chemical vapor generation (CVG) is one of the most mature sampling techniques, which converts analyte to volatile species so as to only introduce the gaseous species to atomic spectrometers. As a result, the separation of analytes from sample matrices and the improvement of sampling efficiency are available, thus yielding high sensitivity and alleviating matrix and spectral interferences when coupled to atomic spectrometry. However, there are more or less impediments remaining in conventional CVG approaches.…”
mentioning
confidence: 99%
“…Over the past few decades, significant efforts have been devoted to developing efficient sampling techniques for improving the sensitivity and anti-interference capability of atomic spectrometry. Chemical vapor generation (CVG) is one of the most mature sampling techniques, which converts analyte to volatile species so as to only introduce the gaseous species to atomic spectrometers. As a result, the separation of analytes from sample matrices and the improvement of sampling efficiency are available, thus yielding high sensitivity and alleviating matrix and spectral interferences when coupled to atomic spectrometry. However, there are more or less impediments remaining in conventional CVG approaches. For example, hydride generation (HG) always requires unstable, expensive, and toxic chemicals, and its efficiency is seriously suppressed by transition metal ions. , Although photochemical vapor generation (PVG) conquers the disadvantages associated with HG to some extent, its application for the analyses of some common hydride forming elements such as Zn has not been successful.…”
mentioning
confidence: 99%